REFLECTIONS ON EROTIZATION AND CHILDHOOD FROM THE ANALYSIS OF ADVERTISEMENTS - Souza Monteiro, Solange Aparecida de [UNESP]; Marcal Ribeiro, Paulo Rennes [UNESP] (Univ Federal Sergipe, 2020)
This paper aims to analyze advertisements and discuss child erotization in content and images of children to disseminate both products that can be used by them and the use of children in advertisements for the adult public. The advertisements make use of different technologies and are disseminated both in print and digital media. To carry out this work we rely on some studies on erotization of children's bodies, presenting elements that build the image of the adult child in the media under the bias of erotization and sensuality, their multiple readings and meanings attributed to them. We consider that these controversial discourses are the engine of early sexuality. We use the theoretical assumptions of the French line discourse analysis. Analyzing this corpus is justified because it is necessary to look at children's advertising with responsibility. Anticipating incompatible attitudes with the age group can promote the decline of childhood, because the child ceases to live a very important stage in human development and can trigger future psychological problems and present difficulties of creativity, socialization and disorders not proper to childhood. We also emphasize that the adultization process refers to the child's distance from the infantile world and early insertion into the adult world, of which they incorporate physical and psychological typologies.
Keywords: Child Erotization; Sexuality in Childhood; Media Speech; Publicity; Advertisement